ATL Server: High Performance C++ on .NET - Kumar, Pranish (Apress, 2012)
IT IS APPARENT THAT WEB APPLICATIONS will play a significant role in the future of software. Today’s business Web sites must be tightly coupled with a company’s other systems, such as databases that track inventory, ordering, and customer and business partner information. All of these business aspects need to be handled in real time over the Web.